2021
DOI: 10.3389/fnins.2021.653325
|View full text |Cite
|
Sign up to set email alerts
|

Increased Resting-State Interhemispheric Functional Connectivity of Posterior Superior Temporal Gyrus and Posterior Cingulate Cortex in Congenital Amusia

Abstract: Interhemispheric connectivity of the two cerebral hemispheres is crucial for a broad repertoire of cognitive functions including music and language. Congenital amusia has been reported as a neurodevelopment disorder characterized by impaired music perception and production. However, little is known about the characteristics of the interhemispheric functional connectivity (FC) in amusia. In the present study, we used a newly developed voxel-mirrored homotopic connectivity (VMHC) method to investigate the interh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…The first is under circumstances where individuals are actively attempting to compensate for problems caused by the disorder, which has been proposed in the case of insomnia (Dai et al ., 2020 ) but could easily additionally be applied in the case of MCI. A study has also reported increased homotopic rsFC in several brain regions (STG and PCC) in individuals with congenital amusia (a neurodevelopmental disorder with impaired perception of music) (Jin et al ., 2021 ) might also reflect attempts at compensation for impairment. In the case of epilepsy, increased homotopic rsFC may reflect the consequence of increased neural activity during seizures and in ADHD it is possible that increases might be contributed to by a proportion of participants taking stimulant medications such as methylphenidate (Ritalin).…”
Section: Common and Distinct Features Of Interhemispheric Functional ...mentioning
confidence: 99%
“…The first is under circumstances where individuals are actively attempting to compensate for problems caused by the disorder, which has been proposed in the case of insomnia (Dai et al ., 2020 ) but could easily additionally be applied in the case of MCI. A study has also reported increased homotopic rsFC in several brain regions (STG and PCC) in individuals with congenital amusia (a neurodevelopmental disorder with impaired perception of music) (Jin et al ., 2021 ) might also reflect attempts at compensation for impairment. In the case of epilepsy, increased homotopic rsFC may reflect the consequence of increased neural activity during seizures and in ADHD it is possible that increases might be contributed to by a proportion of participants taking stimulant medications such as methylphenidate (Ritalin).…”
Section: Common and Distinct Features Of Interhemispheric Functional ...mentioning
confidence: 99%
“…Aphasia is a disease with similar neural mechanism and pattern of symptoms to amusia, these findings are of certain reference value for music and amusia. Increased inter-hemisphere connectivity was also reported in amusia (Albouy et al, 2013;Jin et al, 2021a). MFG_IFS is adjacent to IFG, and it was demonstrated right (which was not certified by peer review) is the author/funder.…”
Section: Discussionmentioning
confidence: 70%
“…All MRI data were collected using a 3T Siemens Skyra scanner at the Second Xiangya Hospital, Central South University. Resting-state functional MRI images and T1-weighted structural images were obtained by echo-planar imaging and magnetization-prepared rapid gradient echo sequence, detailed scanning parameters were reported in our published articles (Jin et al, 2021a;Jin et al, 2021b). Diffusion MRI was acquired along 64 directions (b = 1000s/mm 2 ) together with non-diffusion weighting (b = 0s/mm 2 ) with following parameters: repetition time = 7 7000 ms, echo time = 86 ms, slices = 60, slice thickness = 2 mm, acquisition matrix = 128 × 128, flip angle = 90° and voxel size = 2 × 2 × 2.5 mm 3 .…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…VMHC values can be used to gain quantitative insight regarding functional connections based on time series correlations between mirrored voxels on either side of the brain. Abnormal VMHC values have been observed in the context of diseases including depression ( 16 ), schizophrenia ( 17 ), congenital amusia ( 18 ), diabetes mellitus ( 19 ), hyperthyroidism ( 20 ), and Parkinson’s disease ( 21 ). As such, measuring VMHC represents a sensitive strategy that can be leveraged to evaluate altered interhemispheric coordination in physiological and pathological contexts.…”
Section: Introductionmentioning
confidence: 99%